2011
DOI: 10.1093/ejechocard/jer142
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of right ventricular functions during cancer chemotherapy

Abstract: There is a subclinical decrease in right ventricular systolic and diastolic echocardiographic indices, although mostly, in the normal range, in a relatively short time interval after onset of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
48
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 38 publications
8
48
0
Order By: Relevance
“…Tanindi et al reported a study in patients with breast cancer and anthracycline-embedded chemotherapy. These patients developed a subclinical decrease in right ventricle systolic and diastolic function shortly after starting chemotherapy [42]. In accordance with our observations, Belham et al [43] reported no increase in the RV Tei index during low-dose anthracycline-embedded chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…Tanindi et al reported a study in patients with breast cancer and anthracycline-embedded chemotherapy. These patients developed a subclinical decrease in right ventricle systolic and diastolic function shortly after starting chemotherapy [42]. In accordance with our observations, Belham et al [43] reported no increase in the RV Tei index during low-dose anthracycline-embedded chemotherapy.…”
Section: Discussionsupporting
confidence: 91%
“…There is only one study reporting sub-clinical decrease in RV systolic and diastolic echocardiographical indices, although mostly in the normal range in 37 patients in a relatively short time interval after onset of chemotherapy with anthracyclines. 52 Evaluation of the right ventricle should include qualitative and quantitative assessments of chamber size (at least RV basal diameter) and right atrial size (area), as well as quantitative assessment of RV longitudinal M-mode-derived tricuspid annular plane systolic excursion ( Figure 2A) and pulsed DTI-derived systolic peak velocity of the tricuspid annulus (s ′ ) ( Figure 2B) and RV radial function (fractional area shortening). 53 It is recommended when technically possible to provide an estimate of RV systolic pressure.…”
Section: Right Ventricular Functionmentioning
confidence: 99%
“…For example, patients with breast cancer followed up by echocardiography had significant decreases in tricuspid annular plane systolic excursion and RV fractional area after only 2 cycles of doxorubicin. 50 Similarly, 29 of 36 (81%) patients with breast cancer receiving doxorubicin and trastuzumab developed greater RV than LV impairment at 12 months by cardiac MRI. 51 The clinical relevance of RV impairment was only recognized after it was associated with higher risk of postimplant RV failure and death in patients with LV assist devices (LVADs).…”
Section: Right Ventricular Involvementmentioning
confidence: 98%